Pengaruh Proactive Personality dan Organizational Support for Career Development terhadap Career Success melalui Career Commitment yang Dimoderasi oleh Self-Efficacy (Studi pada PT Bogasari ISM Flour Mills Tbk. Surabaya) - Kusuma, Revan Jaya; Yulianti, Praptini (Jurnal Bisnis dan Keuangan, 2019)
Career success is a way for individuals to fulfill their needs for achievement and effort during work, even career success is someone’s goal in working. The sample in this study were 65 production department employees with quantitative analysis approaches. In this study using PLS (Partial Least Square) analysis with SmartPLS 3.0 software. Research on career success benefits both individuals and organizations. At the individual level, career success can be observed from the objective (extrinsic) and subjective (intrinsic). Knowledge of career success helps individuals de- velop the right strategies to commit to careers in their working days. At the organizational level, knowledge of the relationship between proactive personality and organizational support for career development towards career success can help companies to design effective career systems. Compa- nies that want to get competent human resources must understand the factors that affect their employees’ career success, one of these factors is self-efficacy. The self-efficacy variable in this study is positioned as a moderator that influences the relationship between career success and career commitment. The purpose of this paper is to develop conceptual models and propose hy- potheses that connect proactive personality and organizational support for career development in career success through career commitment that is moderated by self-efficacy.